Coplanar strip line-fed series dipole array antenna for high-gain realization - Wang, Heesu; Park, Ikmo (IEEE Transactions on Antennas and Propagation, 2021)
In this communication, we present a coplanar strip (CPS) line-fed series dipole array antenna for high-gain realization. Printed dipoles of the same size are connected using the CPS line, and impedance matching is achieved with an integrated balun. The gain of the designed array antenna is increased by approximately 2.6 dB as the number of dipoles is doubled. Unlike the conventional endfire array, which has no gain increment beyond a certain number of radiation elements, the gain of the proposed array antenna continuously increases in proportion to the number of dipoles. A CPS line-fed series array antenna with 32 dipole elements was fabricated and evaluated. The measured gain of the 32 dipole array antenna at a center frequency of 15 GHz was 17.4 dBi, the measured −10 dB impedance bandwidth was 9.1-21.6 GHz, and the measured 3 dB gain bandwidth was 13.4-17.4 GHz. The dimensions of the designed dipole array antenna are 0.7 λo×13.2 λo×0.0063 λo, where λo is the free space wavelength at the center frequency.
Keywords: Array antennas; Center frequency; Coplanar strip line; Coplanar strips; End-fire array; Free-space wavelengths; Impedance bandwidths; Printed dipole; Endfire antenna; High-gain antenna; Printed dipole array; Series-fed antenna